2022
DOI: 10.1093/oncolo/oyac131
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Geriatric Assessment and Post-Chemotherapy Functional Status in Older Patients with Cancer

Abstract: Background Maintaining functional status is among the most important patient-centered outcomes for older adults with cancer. This study investigated the association between comprehensive geriatric assessment (CGA) and progressive disease or decline of IADL-independence 1 year after chemotherapy, overall survival (OS), and premature termination of chemotherapy. CGA-based functional status and quality of life (QOL) 1 year after chemotherapy are also described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…CGA and the geriatric G8 screening assessments were performed before and after the completion of chemotherapy. They found that an abnormal geriatric G8 score before chemotherapy was a risk factor for a decline of IADL-independence (OR 3.60, 95% CI 1.98–6.54, p < 0.0001), prematurely terminated chemotherapy (OR 2.12, 95% CI 1.24–3.65, p = 0.006), and shorter median OS (HR 1.71, 95% CI 1.16–2.52, p = 0.007) especially in patients with solid malignancies 33 . These data, as well as our analysis, confirm the interdependence between IADL and geriatric G8 score, and how much the impairment in daily activity and cognition might impact treatment and clinical outcomes in older cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…CGA and the geriatric G8 screening assessments were performed before and after the completion of chemotherapy. They found that an abnormal geriatric G8 score before chemotherapy was a risk factor for a decline of IADL-independence (OR 3.60, 95% CI 1.98–6.54, p < 0.0001), prematurely terminated chemotherapy (OR 2.12, 95% CI 1.24–3.65, p = 0.006), and shorter median OS (HR 1.71, 95% CI 1.16–2.52, p = 0.007) especially in patients with solid malignancies 33 . These data, as well as our analysis, confirm the interdependence between IADL and geriatric G8 score, and how much the impairment in daily activity and cognition might impact treatment and clinical outcomes in older cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight that age alone should not preclude considerations of chemotherapy. A validated functional assessment tool, such as the comprehensive geriatric assessment (CGA), can be used to identify fit elderly patients who are able to receive chemotherapy and should be introduced into clinical practice ( 29 , 30 ). Our findings suggest that elderly patients should be considered for chemotherapy, and chemotherapy regimens should deviate according to each individualized patient’s performance or medical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Though the evidence supporting the use of CGA is already convincing in oncology [37][38][39], the lack of geriatricians is the most frequent reason for not using CGA in daily routine [40]. If a geriatrician is not available, at least a geriatric screening should be implemented to identify those in risk of frailty [41][42][43].…”
Section: Discussionmentioning
confidence: 99%